Features of the response to inflammatory process in children with high and low intensity of free radical oxidations in lymphocytes during the acute period of the disease in various ethnic groups - V. V. Ivanova; L. V. Govorova; A. V. Erbasskaya; L. A. Alekseeva (Журнал инфектологии)
Acute phase response represents a constellation of local and systemic reactions of the organism to the tissue damage caused by various reasons – infection, trauma, inflammation, tumor growth. So-called proteins of acute phase have a special value among the factors causing some changes in the case of inflammation. In the article the features of acute phase response to the inflammation and regulating role of adaptation hormones in the case of acute respiratory infection complicated by pneumonia in children living in the conditions of Far North (Yakutia) among the native population and the arrived one werer characterized. 112 children with acute respiratory infection accompanied by pneumonia and 42 practically healthy ones have been examined in the conditions of Far North. Both Russian and local population is forced to fight with pneumonia by the activation of free radical oxidation, i.e. usage of «respiratory explosion» reactions to get protected against inflammatory processes. The intensity difference in the biochemical response among the members of the two ethnic groups of patients is identified. Some considerable changes in С-reactive protein level, especially among Russians in the group with a high level of free radical oxidation (10 times above normal level) are noted. Higher level of α-2-macroglobulin among children with a low level of free radical oxidation is also observed in the group of Russian children. The levels of transferrin and prealbumin are characterized by a valid increase only during the period of reconvalescence, after their synthesis activation by glucocorticoids the level of which is already increased during the acute period. The conducted research has confirmed valid shifts of adaptation hormone level, acute phase proteins and free radical oxidation processes in blood of children with cute respiratory infection accompanied by pneumonia in the conditions of Far North. More expressed changes can be observed among the children of the arrived population, as being less adapted for the conditions of Far North.